Validating students' library experience survey using rasch model - Scoulas, Jung Mi; Dünya, Beyza Aksu; De Groote, Sandra L.; Dünya, Beyza Aksu (Elsevier Science Inc, 2021)
Few studies have investigated the psychometric property of new instruments developed locally to assess students' library experience, such as their behavior, perception and attitude toward library use. Validating a survey instrument is critical because using untested assessment instruments is more likely to lead to a lack of credibility in the results, as well as a lack of accuracy in the study's purpose (Sullivan, 2011). This study used data from a locally developed student library experience survey distributed in Spring 2018 at a large public research university library to examine undergraduate and graduate students' behaviors, attitudes and perceptions of library use. To test the validity of the survey as to whether six subdomains of the library experience survey contributed to a single construct, library experience, the study used Rasch model framework. This study contributes to the field as a first example using the Rasch model for library assessment purposes. Suggestions for best practices are discussed.
Keywords: Survey Instrument; Library Experience; Validity; Rasch Model